PERANAN IKATAN FLOBAMORA DALAM TRADISI ADAT MASYARAKAT MANGGARAI DI DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Fransiska Ima Kulada Kefi; Isjoni Isjoni; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Seeing the increasing number of family households from Flores, East Nusa Tenggara, that settled in Duri, so as to clarify the direction or purpose of both resolving the issue of adat, especially marriage and so on, as well as the feeling of being together and loving the homeland, plus due to the development of the times that affected the change, the number of Flores people who married tribes outside the area of origin because of migrating, so that the young generation of Flores in Duri still did not know the traditions of their respective regions, especially Manggarai, making the Flores community various tribes in Duri took the initiative to establish an organization or association called the Association of Flobamora. The purpose of this research is to find out the background of the formation of Flobamora in Duri Mandau Subdistrict, to find out the views of Flores people, especially Manggarai, on the existence of Flobamora in Duri, Mandau Subdistrict and to know the role of Flobamora in the Manggarai tradition in Duri, Mandau Subdistrict. Mandau community towards the existence of Flobamora. The research uses qualitative research and data collection techniques in the form of literature, documentation, observation and interviews.The results of this study indicate that the Flobamora Association took part in the indigenous traditions of the Manggarai Flores community, some of which were still carried out in Duri Mandau District as being a liaison for fellow Flores people who wanted to get married, mediators in every issue and driver of customary values every tradition by the Flobamora community itself.Key Words: Flobamora, Tradition, Role